Preparation, Characterization And Properties Of Polypropylene/Muscovite Nanocomposite - Rasyid, Mohd Fadli Ahmad (2012)
In this study, polymer layered silicate nanocomposites containing polypropylene (PP), compatibilizer and organomuscovite were prepared by melt compounding. Polypropylene grafted maleic anhydride (PP-g-MAH) and polypropylene methyl polyhedral oligomeric silsesquioxane (PP-POSS) were used to compatibilize PP/muscovite systems. Muscovite clay particles were initially treated with lithium nitrate (LiNO3) and followed by cetyltrimethylammonium bromide (CTAB) through ion exchange treatment to obtained organomuscovite (OM).